ANALISIS PENGHITUNGAN, PENCATATAN, DAN PELAPORAN PAJAK PENGHASILAN PASAL 23 ATAS JASA OUTSOURCING (Studi Kasus Pada PT XYZ) - Azizah, Nadya Nurâ€™ (Jurnal Mahasiswa Perpajakan, 2015)
Research about the analysis of Income Tax Article 23 for outsourcing at PT XYZ is aimed to understand and to analyze calculation, registration and reporting of Income Tax Article 23 for Outsourcing Service at PT XYZ to ensure whether the process has been in compliant or deviant with Law No.36/2006 about Income Tax. Result of research indicates that the calculation, registration and reporting of Income Tax Article 23 for outsourcing service at PT XYZ is not yet complying with Law No.36/2006 about Income Tax. The author also has found that the calculation of Income Tax Article 23 for outsourcing service at PT XYZ is not comparable with the determination of DPP taxbase for Income Tax Article 23 for outsourcing service. PT XYZ seems negligent from registering prepaid tax Article 23 such that the company does not submit Annual Income Tax Return to the Tax Service Office. PT XYZ as the provider of outsourcing service that must be subjected to Income Tax Article 23 for outsourcing service shall be proactive problem-solver in the case of mistaken calculation of Income Tax Article 23 for outsourcing service. PT XYZ has performed the registration for Profit-Loss and also prepared Balance Sheet. Keywords: Income Tax, Income Tax Article 23, Outsourcing Service ABSTRAK Penelitian tentang analisis perlakuan Pajak Penghasilan Pasal 23 atas jasa outsourcing pada PT XYZ bertujuan untuk mengetahui dan menganalisis penghitungan, pencatatan, dan pelaporan Pajak Penghasilan Pasal 23 atas jasa outsourcing pada PT XYZ telah sesuai atau tidak sesuai dengan UU PPh Nomor 36 Tahun 2008. Hasil dari penelitian ini yaitu pelaksanaan penghitungan, pencatatan, dan pelaporan PPh Pasal 23 atas jasa outsourcing pada PT XYZ belum berjalan optimal sesuai dengan dengan Undang-Undang No. 7 Tahun 1983 sebagaimana telah beberapa kali diubah terkahir dengan Undang-Undang Nomor 36 Tahun 2008 tentang Pajak Penghasilan. Peneliti juga menemukan bahwa penghitungan PPh Pasal 23 atas jasa outsourcing pada PT XYZ belum sesuai dalam menentukan DPP PPh Pasal 23 atas jasa outsourcing, PT XYZ belum mencatat atas prepaid tax pasal 23 sehingga tidak melaporkan SPT PPh Badan ke Kantor Pelayanan Pajak yang terdaftar. PT XYZ sebagai penyedia jasa outsourcing yang wajib dipotong PPh Pasal 23 atas jasa outsourcing harus aktif dalam hal apabila terjadi kekeliruan penghitungan dalam pemotongan PPh Pasal 23 atas jasa outsourcing. PT XYZ harus melaksanakan pencatatan dalam Laba Rugi dan Neraca. Â  Kata Kunci: Pajak Penghasilan, Pajak Penghasilan Pasal 23, Jasa Outsourcing